Investigating diversity in European audiences for public engagement with research: Who attends European Researchers Night in Ireland, the UK and Malta? - Roche, Joseph (My University, 2021)
European Researchers’ Night is an annual pan-European synchronized event devoted to public engagement with research. It was first held in 2005 and now occurs in over 400 cities across Europe, with the aim of bringing researchers closer to the general public. To investigate social inclusion in these events, we conducted survey research across three national contexts (Ireland, Malta and the UK) and events in seven cities between 2016 and 2019 (n = 1590). The results from this exploratory descriptive study confirmed one hypothesis, namely that event attendees had substantially higher levels of university qualification than the national publics. This is in line with wider patterns of unequal participation in public engagement with research activities based on socio-economic status. However, we also found mixed evidence on the prevalence of ethnic minority representation among event attendees compared to the general population, thus failing to uphold the second hypothesis that predicted an over-representation of white majority participants. This second finding diverges from existing research findings about ethnic diversity amongst science communication audiences, raising the possibility that some public engagement events are over-performing on this dimension of social inclusion. Overall, the findings demonstrate that European Researchers’ Night has potential for addressing the critical goal of enhancing the diversity of audiences for public engagement with research, even as it falls short on the key metric of socio-economic diversity.
PUBLISHED
Keywords: Public engagement; Research; Europe; Inclusive Society; Informal Science Education; Non-formal Science Education; Public Engagement in Science; Public Engagement with Science; SCIENCE COMMUNICATION; Science & Society; Science Education; Science Shows